The Correlation Between Students’ Grammar Mastery and Students’ Speaking Skills of the Tenth Grade Students at Man 2 Palu - Windiani; Kuliahana, Ana; Fatima (UNESA, 2025)
Grammar mastery is considered an important foundation in constructing proper and communicative sentences. Based on that, this study aimed to find out whether there is a correlation between students' mastery of grammar and their speaking ability. This research used a quantitative approach with a correlational design. The sample consisted of 31 grade X students who were selected using a purposive sampling technique. The results showed that there was a high correlation between students' grammar mastery and their speaking ability. The significance value of 0.000 is below the significance level of 0.05, and the correlation coefficient (r) value of 0.776 is greater than the r table value, which is 0.3550. This means the alternative hypothesis is accepted and the null hypothesis is rejected. It is shown that the higher the students' mastery of grammar, the better their speaking ability. Therefore, it can be concluded that there is a correlation between students’ grammar mastery and students’ speaking skills of the tenth-grade students at MAN 2 Palu in the academic year 2024/2025.